2015
DOI: 10.1103/physrevlett.114.110501
|View full text |Cite
|
Sign up to set email alerts
|

Microwave Experiments Simulating Quantum Search and Directed Transport in Artificial Graphene

Abstract: A series of quantum search algorithms have been proposed recently providing an algebraic speedup compared to classical search algorithms from N to ffiffiffiffi N p , where N is the number of items in the search space. In particular, devising searches on regular lattices has become popular in extending Grover's original algorithm to spatial searching. Working in a tight-binding setup, it could be demonstrated, theoretically, that a search is possible in the physically relevant dimensions 2 and 3 if the lattice … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
1
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 38 publications
0
28
1
1
Order By: Relevance
“…The electric current imported from the side of the PC excites the localized modes at the Dirac frequency. This structure is different from that of Refs [21][22][23]26], where the PCs are thin slabs with non-negligible thickness effects.…”
Section: Experimental Studycontrasting
confidence: 72%
See 1 more Smart Citation
“…The electric current imported from the side of the PC excites the localized modes at the Dirac frequency. This structure is different from that of Refs [21][22][23]26], where the PCs are thin slabs with non-negligible thickness effects.…”
Section: Experimental Studycontrasting
confidence: 72%
“…Edge modes were found in these studies. Meanwhile, J. Böhm et al [26] demonstrated the implementations of the continuous quantum wave search algorithms and directed wave transport in artificial graphene lattice. In this ingenious experiment, localized search states were brought into resonance with an extended lattice state near the Dirac point.…”
Section: Introductionmentioning
confidence: 99%
“…All these lattices have attracted the attention of researchers. For instance, coined quantum walks were analyzed on the two-dimensional square lattice [10][11][12][13][14][15], hexagonal lattice [16][17][18][19], and triangular lattice [19][20][21]. Since the seminal paper by Shenvi et al [22], coined quantum walks are being used for search algorithms [23].…”
Section: Introductionmentioning
confidence: 99%
“…The advantages of this scheme is that it requires no extended initial state and also the walkers do not oscillate in-and-out of the marked vertex, thus we can measure at any time, after the initial waiting period. However, like another experimental scheme [13], we have no reduction in the number of vertices needed so there is no resource advantage over the Grover search.…”
Section: Driven Dtqw Searchmentioning
confidence: 99%
“…They have also been used to model transport processes such as quantum heat transport [7] and percolation [8]. Various experimental implementations have also been explored in optical delay loops [9][10][11], trapped atoms [12], microwave scattering [13] and waveguide arrays [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%